Escrevivendo insubmissos verbos de vida com jovens negras na socieducação - Silva, Ketle (2021)
Every day we experience the consequences of an inconclusive abolitionism in which the once enslaved black body was put on the margins of society without any policy of reparation. As an effect, the Brazilian black population occupies the base of the pyramid in unequal conditions of housing, health, education, infrastructure, work, salary, culture, leisure. On the other hand, in the prison and socio-educational systems occupy the top of the pyramid and the politics of war on drugs is more configured as a euphemism for the mass imprisonment of the black population, historically marked by the brutality of violence. Therefore, the present work embodies a critical perspective to the punishment logic that permeates the socio-educational system directed to adolescents who have committed infractions, considering that, although we have advanced in some aspects with the implementation of the Child and Adolescent Statute, there is still a long way to struggle against a system that punishes and put in prison mostly black youth. Thus, we see how racism structure its functioning through devices ordered to ensure the maintenance of inequalities based on racial hierarchy, denouncing the faces of one same State: that allegedly should guarantee the integral protection, another, which produces a series of violations of rights prior to the infraction. Based on these reflections, the present work sought to construct narratives with adolescents in compliance with socio-educational measures in an open environment at the Specialized Reference Center of Social Assistance (CREAS) in the city of Vitória-ES, proposing to understand how the different social markers of race, class and gender are articulated in their experiences. The tool concept of Conceição Evaristo's escrevivência and black feminist thought is used as an inspiration, thus assuming a feminine and black writing to displace the very field of knowledge and intellectuality oriented in Eurocentric paradigms that suppress other forms of knowledge.